Association of ABO Blood Groups with Diabetes Mellitus - Mohammed. L.A. Al-Baaj Al-Baaj (Journal of Global Pharma Technology, 2018)
The aim of this study is to highlight the potential relationship between blood groups and diabetes for the local population of the city of SuqAl-Shuyukh in Thi-Qar, Iraq. The study included the identification of blood groups to 276 diabetes patients for the period from December 2018 to March 2018. ABO blood groups of all subjects were determined by slide agglutination method. Chi- square statistical analysis among different blood groups between non-diabetic (n= 100) and diabetic population (n= 276) revealed no significant relationship of any blood group with diabetes mellitus (p ˃ 0.05). But relative risk (RR) were calculated in reference to blood group O, it has been observed that slight increase of risk of developing diabetes mellitus among AB (RR 1.111), a (1.045) and B (1.025).Keywords: Diabetes Mellitus (DM), ABO Blood Groups, A, B, AB, O.